The Effectiveness of Implementing The Khalifatullah Fill Ardh Philosophy in Increasing Financial Transparency - Uyun, Jamilatul; Kusuma, Nailah Aka (Islamic Micro Finance Journal, 2024)
Financial transparency is a crucial element of good governance and organizational accountability. One philosophy that can be applied to enhance financial transparency is the Khalifatullah Fill Ardh concept. This research aims to evaluate the effectiveness of the Khalifatullah Fill Ardh philosophy in improving financial transparency in mosques. The study employs a qualitative method with a descriptive approach, focusing on the Al-Ikhwan Mosque as its research object. The findings reveal that the takmir (management board) of the Al-Ikhwan Mosque has not effectively implemented the principles of the Khalifatullah Fill Ardh philosophy, which include the traits of apostleship (siddiq, amanah, tabligh, and fathanah). Moreover, financial management and accountability are centralized under the chairman of the takmir, resulting in insufficient financial transparency and accountability within the mosque. Future research is encouraged to explore the application of other principles of the Khalifatullah Fill Ardh concept to enhance financial transparency, using the same or different research objects